Performance of the long-snouted seahorse, Hippocampus guttulatus, under warming conditions - Costa, Ana Beatriz; Correia, Miguel; Silva, Gonçalo; Lopes, Ana Filipa; Faria, Ana Margarida (Frontiers in Marine Science, 2023)
Temperature is a determinant cue for several behavioral, physiological, and metabolic processes in fish, which occur within a range set to optimize species fitness. Understanding how ocean warming will impact species, at individual and population levels, is, therefore, of utmost relevance for management and conservation purposes. This knowledge assumes particular relevance when it comes to species with unique life history traits that experience multiple threats, such as seahorses. This study aimed to assess the effects of warming on growth, feed intake, and behavioral patterns of the long-snouted seahorse, Hippocampus guttulatus. Fish were collected, before the breeding season, in the Sado estuary, Portugal, and subsequently exposed for an 8-week period to three different temperatures: 17ºC, 20ºC, and 24ºC. Three times a week, behavioral observations were performed. Feed intake was measured every day and individuals were weighed once a week. Results indicate differences in behavioral responses of seahorses exposed to increasingly warming conditions. Under extreme temperature conditions (24 ºC), fish were more active, and fed more, but this increment of energy through feeding did not translate into increased growth in weight. Altogether, these results indicate that Sado’s population of H. guttulatus may become under thermal stress when exposed, for a long term, to warming conditions that are expected to occur by the end of the century.